Optical Coherence Tomography (OCT): Imaging the Visual Pathway as a Model for Neurodegeneration - Galetta, Kristin M. (Springer-Verlag, 2011)
Axonal and neuronal degeneration are important features of multiple sclerosis (MS) and other neurologic disorders that affect the anterior visual pathway. Optical coherence tomography (OCT) is a non-invasive technique that allows imaging of the retinal nerve fiber layer (RNFL), a structure which is principally composed of ganglion cell axons that form the optic nerves, chiasm, and optic tracts. Since retinal axons are nonmyelinated until they penetrate the lamina cribrosa, the RNFL is an ideal structure (no other central nervous system tract has this unique arrangement) for visualizing the processes of neurodegeneration, neuroprotection and, potentially, even neuro-repair. OCT is capable of providing high-resolution reconstructions of retinal anatomy in a rapid and reproducible fashion and permits objective analysis of the RNFL (axons) as well as ganglion cells and other neurons in the macula. In a systematic OCT examination of multiple sclerosis (MS) patients, RNFL thickness and macular volumes are reduced when compared to disease-free controls. Conspicuously, these changes, which signify disorganization of retinal structural architecture, occur over time even in the absence of a history of acute demyelinating optic neuritis. RNFL axonal loss in MS is most severe in those eyes with a corresponding reduction in low-contrast letter acuity (a sensitive vision test involving the perception of gray letters on a white background) and in those patients who exhibit the greatest magnitude of brain atrophy, as measured by validated magnetic resonance imaging techniques. These unique structure–function correlations make the anterior visual pathway an ideal model for investigating the effects of standard and novel therapies that target axonal and neuronal degeneration. We provide an overview of the physics of OCT, its unique properties as a non-invasive imaging technique, and its potential applications toward understanding mechanisms of brain tissue injury in MS, other optic neuropathies, and neurologic disorders. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13311-010-0005-1) contains supplementary material, which is available to authorized users.